Pembuatan dan Deploy API di Google Cloud Platform Menggunakan Cloud Run Services - Oswaldo Da Conceicao; Yasinta O. L. Rema; Budiman Baso; Guido Adolfus Suni (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research discusses the development, testing, and deployment of a backend API using Google Cloud Platform (GCP), with Firestore as the database and Cloud Storage for storing user profile photos. The API was developed using Express.js, integrated with Firestore and Cloud Storage, and tested for functionality using Postman. Deployment is done to Cloud Run via creating a Dockerfile and building a Docker image. Test results showed that the API was able to handle 7,875 requests in five minutes, with an average of 25.64 requests per second and an average response time of 97 ms. All endpoints are stable, responsive, and error-free. This research focuses on the application of cloud technology to the development of sign language applications, and shows that the use of GCP services can produce efficient and scalable API solutions. These results are significant in supporting the development of cloud-based applications to meet user needs effectively, especially in mobile applications that require reliable backend services.